Meningkatkan Hasil Belajar PAI dengan menggunakan Metode Diskusi di Kelas VI SD Negeri 08 Ganggo Mudiak - Gustina, Rini (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) for sixth-grade students at SDN 08 Ganggo Mudiak through the application of discussion methods supported by audio-visual media. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, encompassing the stages of planning, implementation, observation, and reflection. The findings revealed that in Cycle I, the students’ learning mastery level reached 63.16%. After improvements in Cycle II, the mastery level increased to 89.47%. This improvement indicates that the discussion method, combined with audio-visual media, can create a more active, participatory, and profound learning experience. The study concludes that employing discussion methods with the support of audio-visual media is an effective strategy to enhance PAI learning outcomes, particularly on the topic of halal and haram in Islam.